THE RELEVANCE OF TRANSFORMATIONAL LEADERSHIP IN THE CONTEXT OF THE COMPETENCE APPROACH IN PRE-SCHOOL - Pakalniņa, Rasa; Ročāne, Maija; Jurs, Pāvels (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
. In the context of the ongoing changes in the education system of Latvia, the principles of learning approach in pre-school education are based on the competence-based approach, as well as the development of transformative skills. To successfully implement change, the need to develop teachers' creativity, entrepreneurship, decision-making, organisational skills, teamwork, cooperation, sociability, risk-taking and assessment, openness to innovation, reflective thinking and leadership skills becomes essential.  Today, it is important for every teacher to strive for professional development and to achieve individual and collective goals. Leadership skills include the ability to motivate others, good communication skills, positive thinking, delegation of responsibilities, creativity, reliability, responsibility, time management, influence, and decisiveness. Change can also be difficult to be accepted and even can become a reason for leaving a teaching job. Leaders who can accept contemporary challenges, communicate effectively with others, and facilitate the development of leadership skills in colleagues become important in every educational institution. The aim of this publication is to research and evaluate the scientific literature on the relevance of transformational leadership, highlighting the need for developing each teacher`s leadership skills.